Defining a Therapeutic Program for Recurrent Acute Pancreatitis Patients with Unknown Etiology. (July 2014) - Neri, Vincenzo; Lapolla, Francesco; Di Lascia, Alessandra; Giambavicchio, Libero Luca
Aim: To define a therapeutic program for mild-moderate acute pancreatitis (AP), often recurrent, which at the end of the diagnostic process remains of undefined etiology. Material and Methods: In the period 2011-2012, we observed 64 cases of AP: 52 mild-moderate, 12 severe; biliary 39, biliary in alcoholic chronic pancreatitis 5, unexplained recurrent 20. The clinical and instrumental evaluation of the 20 cases of unexplained AP showed 6 patients with biliary sludge, 4 microlithiasis, 4 sphincter of Oddi dysfunction, and 6 cases that remained undefined. Results: Among 20 patients with recurrent, unexplained AP at initial etiological assessment, we performed 10 video laparo cholecystectomies (VLCs), 2 open cholecystectomies and 4 endoscopic retrograde cholangiopancreatography/endoscopic sphincterotomies (ERCP/ES) in patients who had undergone previous cholecystectomy; 4 patients refused surgery. Among these 20 patients, 6 had AP that remained unexplained after second-level imaging investigations. For these patients, 4 VLCs and 2 ERCP/ES were performed. Follow-up after six months was negative for further recurrence. Conclusion: The recurrence of unexplained acute pancreatitis could be treated with empirical cholecystectomy and/or ERCP/ES in cases of previous cholecystectomy.